Homeland Defense. Steps Have Been Taken to Improve U.S. Northern Command's Coordination with States and the National Guard Bureau, but Gaps Remain - GOVERNMENT ACCOUNTABILITY OFFICE WASHINGTON DC (2008)
In 2002, the Department of Defense (DOD) established U.S. Northern Command (NORTHCOM) to conduct homeland defense and civil support missions in and around the United States. It is important that NORTHCOM coordinate with the National Guard Bureau (NGB), because NGB has experience dealing with state and local authorities during incidents and functions as NORTHCOM's formal link to the states. GAO was asked to (1) determine the extent to which NORTHCOM has ongoing efforts to coordinate with the states and NGB in planning, exercises and other preparedness activities and (2) identify the extent to which there are any gaps in this coordination. To do this, GAO surveyed the state adjutants general, the highest ranking guardsman in each state, and received a 100 percent response rate, and reviewed interagency coordination plans and guidance.